Evaluation of Peel Ply Effectiveness in Controlling Mould Release Agent Contamination of Epoxy/Carbon Fibre Composite Laminate Surfaces - R.R.P. Kuppusamy; A. Zade; B. Sridhar Babu (Archives of Metallurgy and Materials)
The peel-ply effectiveness in controlling the mould release contaminations of resin transfer molded (RTM) RTM6/G0926 epoxy-carbon fibre composite laminate surfaces have been examined. X-ray photoelectron spectroscopy (XPS) was employed to evaluate the extent of transfer of mould release agents and other surface contaminants of RTM composite laminates at semi-cured and fully cured states. Fully cured and 55% semi-cure degree of RTM composite laminates were prepared using polyester and diatex peel plies. The effectiveness of polyester and diatex peel plies were evaluated by comparing the amount of Frekote mould release contaminants present in the laminate surfaces processed with and without peel plies. The XPS results shows that the composite laminates processed without peel plies at different cured states exhibit uniform contamination with Freakote calcium metal ions. At the comparisons of polyester and diatex peel plies, the diatex peel ply performs better in controlling the surface contaminations.